The effect of magnetic annealing on barrier asymmetry in Co40Fe40B20/MgO magnetic tunnel junctions - COEY, JOHN MICHAEL DAVID; FENG, JIA-FENG (My University, 2010)
We demonstrate that high-quality magnetic tunnel junctions with Co40Fe40B20 electrodes and crystalline MgO barriers, which show a 230% tunneling magnetoresistance ratio at room temperature, can be successfully fabricated by using a target-facing-target sputtering technique and present the results on the change of barrier asymmetry after the annealing at different temperatures. Bias voltage dependence of magnetoresistance ratio for Co40Fe40B20/MgO magnetic tunnel junctions is highly asymmetrical in the as-deposited states and becomes more symmetrical after magnetic annealing. It also exhibits a shift of the tunneling magnetoresistance maximum to a positive bias voltage under the low-temperature annealing.
PUBLISHED
Keywords: Magnetic tunnel junction; Tunneling magnetoresistance; MgO barrier